STRATEGI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DALAM MENGEMBANGKAN KREATIVITAS SISWA DI SMK PGRI 11 CILEDUG KOTA TANGERANG - Wakid; Amsori; Encep (Jurnal Riset Multidisiplin Edukasi, 2025)
This research is motivated by the urgency of Islamic Religious Education (PAI) learning strategies to foster student creativity in the digital era. SMK PGRI 11 Ciledug was selected as the study location due to the variety of strategies implemented there. The main objective is to analyze effective strategies, identify supporting and inhibiting factors, and examine their impact on the development of religious character. Using a descriptive qualitative methodology with data collection through interviews, observation, and documentation, the research findings indicate that the effective strategies are a combination of a contextual approach, Project-Based Learning (PjBL), digital technology integration, and collaborative methods. Further analysis reveals that both internal factors (teacher competency, technological literacy) and external factors (school support, facilities) significantly influence the success of these strategies. This affirms that holistic PAI planning plays a crucial role in enhancing student creativity and shaping their religious character.